Права женщин на землю в Кыргызской Республике. Защита прав женщин на ресурсы с помощью гендерно-трансформационных подходов - Global Initiative for Gender Transformative Approaches for Securing Women’s Resource Rights (2023)
This series of socio-legal reviews summarizes the legal and policy documents related to women’s land tenure in seven countries: Kyrgyzstan, Uganda, The Gambia, Ethiopia, Niger, Bangladesh, and Colombia. These synthesis documents, part of the IFAD Initiative on Women’s Resource Rights, are designed for researchers and policymakers seeking to improve women’s land and resource rights in these target countries. This review covers: • A general characterization of land and resource tenure systems at national, regional, and local levels • Existing institutional and regulatory frameworks for land and resource tenure, and the extent to which these are inclusive of women • Implemented land tenure interventions, and the extent to which these benefit women • Barriers and constraints affecting women’s ability to access rights • Mechanisms for dispute resolution, and how these engage women and address their concerns